Pengaruh Model Creative Problem Solving Terhadap Kemampuan Pemecahan Masalah Matematika Siswa Sekolah Dasar - Siti Huzayfah (Jurnal Inovasi Pendidikan Dasar, 2017)
The aim of this study is to determine the effectiveness of Creative Problem Solving (CPS) on problem solving skill of mathematics students. This study was quantitative study with quasi experimental design type nonequivalent control group design. The data were collected through problem solving test. Partisipants of this study were 56 students on third grade in Sekolah Dasar Negeri Kebayoran Lama Utara. They were separated into two groups; 28 students in experimental group and 28 students in control group. The experimental group was treated by CPS learning, while the control group was treated by traditional learning. The study was conducted in the even semester of the academic year 2016/2017. The data was analyzed using t-test. The result showed that there was a significant difference in problem solving skill between the experimental and the control class. The average of problem solving skill in experimental group was higher than control group. Herewith, it has been concluded that CPS had an effect on students’ problem solving skill.